Interdependence between the elites and the poor in contexts of high inequality: conceptual and empirical issues - Lopez, Matias (Universidade Estadual Paulista / UNESP, 2020)
In this essay I propose a discussion about the social interdependence between elites and the poor in unequal democracies. Following the theoretical arguments of Norbert Elias, Abraham de Swaan and Elisa Reis, I point to mechanisms capable of leading elites toward feelings of interdependence between them and the poor. Among such mechanisms, I highlight the effect of negative externalities such as urban violence and epidemics. I also review recent research about elite values and strategies toward poverty and inequality in Brazil, in contrast with other experiences of late modernization, especially in Latin America but also in Asia and Africa. My argument is that the perception of negative externalities may be a necessary condition, while certainly insufficient, for the emergence of feelings of interdependence capable of mobilizing the elite toward democracy and distribution.